An integrated conceptual model of environmental needs for New Zealand children's active travel to school. (March 2020) - Smith, Melody; Ikeda, Erika; Hawley, Greer; Mavoa, Suzanne; Hosking, Jamie; Egli, Victoria; Zhao, Jinfeng; Mackay, Lisa; Donnellan, Niamh; Amann, Rebecca; Mackie, Hamish; Witten, Karen
Abstract: Introduction: Active school travel (AST) is important for child and environmental health. In New Zealand, AST has declined over recent decades and is relatively low compared to many other countries. A plethora of evidence related to children's AST exists, yet a holistic and context-specific understanding of factors related to the behaviour remains elusive. The aim of this study is to triangulate data from children, their parents, school representatives, and objectively-assessed environmental features to generate a model that enables a comprehensive understanding of associates of AST in New Zealand children, how these variables interrelate with each other, and where change can occur. Methods: Data were drawn from recent investigations conducted with children, parents/caregivers, and school representatives, and studies examining objectively-assessed built environment characteristics in relation to AST. Findings were summarised, aggregated, and triangulated, with a focus on themes where consistent findings were observed across data sources or respondents (i.e., children, parents, school representatives, geographic information systems (GIS)-derived variables). Links between variables were investigated and integrated into the final model. Results: Distance from home to school and ensuring child safety were prevailing factors associated with children's AST. School policies, practices, partnerships and culture play an integral role in supporting children's AST, and in some cases can mitigate environmental barriers. An active community culture, positive neighbourhood social relations, and links between the school and community are important elements to support AST. Conclusion: This research demonstrates the complexity of AST and reinforces that interventions for increasing active travel modes need to be multi-faceted and not isolated projects. Cross-sector approaches that are sustained over time are needed to facilitate meaningful change in AST. Strategic resourcing and national targets for AST rates may be effective ways to harness commitment across sectors and ensure actions to address the needs presented are operationalised. Graphical abstract: Image 1 Highlights: Active school travel (AST) is low in New Zealand children. Determinants of low active school travel are complex, as are potential solutions. Distance to school and safety concerns are key barriers to active school travel. School/community culture, partnerships, and practices are enablers of active school travel. Strategic resourcing for leadership and social and infrastructural interventions is needed.